2016
DOI: 10.1093/humrep/dew056
|View full text |Cite
|
Sign up to set email alerts
|

Depolarization of sperm membrane potential is a common feature of men with subfertility and is associated with low fertilization rate at IVF

Abstract: STUDY QUESTIONAre significant abnormalities in outward (K+) conductance and resting membrane potential (Vm) present in the spermatozoa of patients undertaking IVF and ICSI and if so, what is their functional effect on fertilization success?SUMMARY ANSWERNegligible outward conductance (≈5% of patients) or an enhanced inward conductance (≈4% of patients), both of which caused depolarization of Vm, were associated with a low rate of fertilization following IVF.WHAT IS KNOWN ALREADYSperm-specific potassium channel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
76
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(80 citation statements)
references
References 28 publications
3
76
1
Order By: Relevance
“…In approximately 10% of the samples from infertile patients there was either a negligible outward conductance or an enhanced inward current, both of which caused Em depolarization. Analysis of clinical data from IVF patients showed a significant association of depolarized Em assessed by patch-clamp with low fertilization rate (Brown et al, 2016). These results point toward the correlation of the Em value of a sperm sample with its fertilizing capacity.…”
Section: Introductionmentioning
confidence: 67%
See 2 more Smart Citations
“…In approximately 10% of the samples from infertile patients there was either a negligible outward conductance or an enhanced inward current, both of which caused Em depolarization. Analysis of clinical data from IVF patients showed a significant association of depolarized Em assessed by patch-clamp with low fertilization rate (Brown et al, 2016). These results point toward the correlation of the Em value of a sperm sample with its fertilizing capacity.…”
Section: Introductionmentioning
confidence: 67%
“…With this in mind, we aimed to analyze whether Em hyperpolarization relates to human sperm fertilizing capacity. It has been recently proposed that a certain degree of Em shift is associated with normal sperm function, as assessed by electrophysiology and IVF outcome (Brown et al, 2016). However, this study involved laborious techniques that hampered the analysis of many cells per patient.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…No ENaC current has been shown in electrophysiological examination of ejaculated cells so far. However, it is worth mentioning that in a recent study where 81 subfertile patients undergoing IVF/ICSI were investigated, one patient that presented depolarized Em associated with low IVF showed a large inward leak conductance (probably Na + ) (19). Unfortunately, this patient did not give permission for genetic analysis.…”
Section: Discussionmentioning
confidence: 98%
“…The regulation of membrane potential (Em) is an important event for fertility (18,19). Brown and coworkers showed that depolarized sperm Em values correlate with a higher percentage of IVF failure (19).…”
Section: Introductionmentioning
confidence: 99%